2006
DOI: 10.1002/sce.20110
|View full text |Cite
|
Sign up to set email alerts
|

Preservice elementary teachers' critique of instructional materials for science

Abstract: Science teachers must adapt curriculum materials, so preservice teachers must develop beginning proficiency with this authentic task of teaching. What criteria do they use when they critique these materials in preparation for adapting them, when they develop the criteria themselves and when they are given a set of criteria from which to choose? These results indicate that the 20 participating preservice elementary teachers held a sophisticated set of criteria for critiquing instructional materials; for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
106
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 44 publications
8
106
0
9
Order By: Relevance
“…While this third study was not a continuation of the second, it nonetheless provided a context in which to explore promising approaches for effective teacher education that could add to my prior findings. Preparing preservice teachers to effectively use curriculum materials is an important issue (Davis, 2006) as curriculum materials play a significant role in both shaping elementary science instruction and guiding beginning teachers (Ball & Feiman-Nemser, 1988;Grossman & Thompson, 2004;Kauffman, Johnson, Kardos, Lui, & Peske, 2002;Mulholland & Wallace, 2005). Unfortunately, many of the current materials are of poor quality (Kesidou & Roseman, 2002;Stern & Roseman, 2004).…”
Section: Study 3: Elementary Teachers and Curriculum Materialsmentioning
confidence: 99%
“…While this third study was not a continuation of the second, it nonetheless provided a context in which to explore promising approaches for effective teacher education that could add to my prior findings. Preparing preservice teachers to effectively use curriculum materials is an important issue (Davis, 2006) as curriculum materials play a significant role in both shaping elementary science instruction and guiding beginning teachers (Ball & Feiman-Nemser, 1988;Grossman & Thompson, 2004;Kauffman, Johnson, Kardos, Lui, & Peske, 2002;Mulholland & Wallace, 2005). Unfortunately, many of the current materials are of poor quality (Kesidou & Roseman, 2002;Stern & Roseman, 2004).…”
Section: Study 3: Elementary Teachers and Curriculum Materialsmentioning
confidence: 99%
“…Nonetheless, just as teacher education experiences can support preservice teachers to negotiate these ideas and learn to teach inquiry-oriented science (Crawford, 1999;Windschitl, 2003), so too can they support preservice teachers' learning to critique and adapt science curriculum materials (Davis, 2006). To put these abilities to use and develop robust pedagogical design capacity (Brown, 2002, in press), preservice teachers must develop a teaching identity in which the active use of science curriculum materials is valued and perceived as role appropriate.…”
Section: Preservice Elementary Teachers' Development Of Curricular Romentioning
confidence: 99%
“…Through our work as elementary science teacher educators and science curriculum developers, we have investigated how preservice elementary teachers use and learn from science curriculum materials (Davis, 2006;Dietz & Davis, in press;Forbes & Davis, in press). We have found Remillard's (2005) model of the teacher -curriculum relationship useful.…”
Section: Preservice Elementary Teachers' Development Of Curricular Romentioning
confidence: 99%
See 1 more Smart Citation
“…Novice science teachers tend to be unaware of students' ideas; when they do start to notice students' ideas, they tend to focus on more basic features like the concreteness or accuracy of these ideas (Schneider & Plasman, 2011). As science teachers gain experience, they are more likely to begin to consider how to build on students' prior ideas during instruction, how to link students' ideas to scientific ideas, and why students might find certain ideas conceptually difficult to learn-all significant content challenges that arise in the course of teaching in this area (Meyer, 2004;Schneider & Plasman, 2011).To develop students' ideas about key scientific concepts, research has also pointed to the importance of determining which instructional strategies and resources would be most beneficial for addressing specific student outcomes; this selection usually occurs through the critical analysis and use of curriculum materials (Davis, 2006;Davis & Smithey, 2009). In particular, research has suggested the importance of ensuring that science teachers can fluently discern which instructional resources to use to target specific learning goals, to provide insight into student thinking, and to address specific student challenges (Carlsen, 1991;Schneider & Plasman, 2011).…”
mentioning
confidence: 99%